Molecular marker identification, antioxidant, antinociceptive, and anti-inflammatory responsiveness of malonic acid capped silver nanoparticle - Fatima, Tehrim; Abrar, Hina; Jahan, Noor; Shamim, Sana; Ahmed, Nazia; Ali, Asma Basharat; Begum, Irshad; Ahmed, Waqas (Frontiers in Pharmacology, 2024)
Nano-sized silver has drawn a great deal of attention in the field of health sciences owing to its remarkable therapeutic applications. Interestingly, the method applied to synthesize nanoparticles and the choice of reagents considerably influence their therapeutic potential and toxicities. Current research has explored the toxicity, anti-inflammatory, antinociceptive, and antioxidant responses of the malonic acid-capped silver nanoparticles (MA-AgNPs (C) by using sodium borohydride as a reducing agent at low temperatures by employing both in vitro and in vivo approaches. Furthermore, it has highlighted the synergistic effect of these novel compounds with conventional anti-inflammatory therapeutic agents. Acute and sub-acute toxicity analysis performed following OECD guidelines showed that the studied MA-AgNPs (C) are safer, and prominent toxic signs have not been detected at the highest studied dose of 2000 mg/kg. Cytotoxicity evaluation through brine shrimp lethality revealed 20 % lethality at the highest concentration of 169.8 µg/ml. Significantly, positive anti-inflammatory and analgesic responses alone as well as synergism with the standard were identified through in vitro as well as in vivo methods which were more potent at a lower dose (200 mg/kg). Notably synergistic outcomes were more pronounced than individual ones, indicating their prominent effect as a feasible drug delivery system. IL-6 and TNF-α assessment in excised paw tissue through RTPCR technique further supported their anti-inflammatory potential. DPPH assay revealed eminent in vitro antioxidant activity which was further corroborated by in vivo antioxidant assessment through evaluation of SOD in excised paw tissue.